Walking Training with Foot Drop Stimulator Controlled by a Tilt Sensor to Improve Walking Outcomes: A Randomized Controlled Pilot Study in Patients with Stroke in Subacute Phase - G. Morone; A. Fusco; P. Di Capua; P. Coiro; L. Pratesi (Stroke Research and Treatment)
Foot drop is a quite common problem in nervous system disorders. Neuromuscular electrical stimulation (NMES) has showed to be an alternative approach to correct foot drop improving walking ability in patients with stroke. In this study, twenty patients with stroke in subacute phase were enrolled and randomly divided in two groups: one group performing the NMES (i.e. Walkaide Group, WG) and the Control Group (CG) performing conventional neuromotor rehabilitation. Both groups underwent the same amount of treatment time. Significant improvements of walking speed were recorded for WG (%) than for CG (%, ) as well as in terms of locomotion (Functional Ambulation Classification score: ). In terms of mobility and force, ameliorations were recorded, even if not significant (Rivermead Mobility Index: ; Manual Muscle Test: ). Similar changes between groups were observed for independence in activities of daily living, neurological assessments, and spasticity reduction. These results highlight the potential efficacy for patients affected by a droop foot of a walking training performed with a neurostimulator in subacute phase.